Nature of Linguistic Sign Syeikh Ahmad al-Fathani: (Tabii Tanda Bahasa dari Kaca Mata Syeikh Ahmad al-Fathani: Suatu Gagasan Pemikiran) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2019)
This paper discusses the linguistic philosophy of one of the great scholars in the Malay world, Syeikh Ahmad al-Fathani. The discussions in this paper lay out questions pertinent to the nature of linguistic signs, and find that Syeikh Ahmad had sophisticated thoughts concerning this matter. His idea can be related to the same notion proposed by the father of modern linguistics, Ferdinand de Saussure. This paper suggests that Syeikh Ahmad should be classified as a linguist who recognized the arbitrariness of linguistic signs, which does not accept the idea of natural relationships between signs and the signified or meaning in linguistics. This means that Syeikh Ahmad's position was pin line with the Basra School, if the relation is seen through the tradition of Islamic scholarship. This also shows that the awareness, of the nature of linguistic signs had already been established in Malayonesia.Keywords: Syeikh Ahmad al-Fathani, Ferdinand de Saussure, linguistic historiography, Malay linguistic historiography, philosophy of language.